Factors influencing the optimal selection of central venous access devices: A qualitative study of health care team members' perspectives - Yuan Sheng; Tinglan Wu; Chunmei Fan; Haixia Hao; Wei Gao (Elsevier, 2022)
Objective: This study aimed to explore health care team members' understanding of the factors influencing the optimal selection of central venous access devices (CVADs). Methods: The data of the study was collected using semi-structured interviews. Twenty-six hospital medical staff (four hospital manager, 15 head nurses, 7 nurse) with experience in peripheral or central catheterization from four regions (Northern China, Southern China, Northwest China, and Qinghai-Tibet China) in China were interviewed between June and October 2021. Content analysis was used to analyze the data. Results: The results revealed five themes and 14 sub-themes. Patients: concerns, resources, requirements, and evaluation (security concerns, support resources, life requirements, evaluation among patients); nurses: awareness, knowledge, and popularizing methods (awareness of intravenous therapy, understanding of professional knowledge, forms of popularizing methods); doctors: support and involvement (support for decision-making, involvement in intravenous work); hospital managers: authority, quality control and continuing education (management of catheterization authority, quality control of intravenous infusion, investment in continuing education) and environment: differences and commonalities (differences in social support, and current commonalities). Conclusion: Nurses and other healthcare team members' understanding, selection, use, and recommendation of CVADs have an indirect effect on patients' decision-making. Therefore, hospital managers and government departments can indirectly strengthen medical team cooperation and improve learning education in order to improve the safety of patients receiving intravenous infusions.